2012
DOI: 10.1186/1477-7827-10-94
|View full text |Cite
|
Sign up to set email alerts
|

A new ovarian response prediction index (ORPI): implications for individualised controlled ovarian stimulation

Abstract: BackgroundThe objective was to present a new ovarian response prediction index (ORPI), which was based on anti-Müllerian hormone (AMH) levels, antral follicle count (AFC) and age, and to verify whether it could be a reliable predictor of the ovarian stimulation response.MethodsA total of 101 patients enrolled in the ICSI programme were included. The ORPI values were calculated by multiplying the AMH level (ng/ml) by the number of antral follicles (2–9 mm), and the result was divided by the age (years) of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 53 publications
2
43
0
3
Order By: Relevance
“…Other parameters have been proposed recently: for example, ovarian response prediction index (ORPI) [32], calculated by multiplying the AMH level (ng/ml) by the number of antral follicles (2-9 mm) and dividing the result by the age (years) of the patient [ORPI = (AMH Â AFC)/ patient age]. The authors concluded that ORPI might be used to improve the cost-benefit ratio of ovarian stimulation regimens by guiding the selection of medications and by modulating the doses and regimens according to the actual needs of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other parameters have been proposed recently: for example, ovarian response prediction index (ORPI) [32], calculated by multiplying the AMH level (ng/ml) by the number of antral follicles (2-9 mm) and dividing the result by the age (years) of the patient [ORPI = (AMH Â AFC)/ patient age]. The authors concluded that ORPI might be used to improve the cost-benefit ratio of ovarian stimulation regimens by guiding the selection of medications and by modulating the doses and regimens according to the actual needs of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Serum FSH and LH concentration were used to calculate FSH/LH ratio. The ORPI was defined by the following equation: ORPI = (AMH × AFC)/Patient age [9].…”
Section: Calculation Of Body Mass Index (Bmi) Fsh/lh Ratio and Ovarimentioning
confidence: 99%
“…According to the retrieved oocyte numbers, ovarian response categories were divided into low response (oocytes ≤3), normal response (4-14 oocytes) and excessive response (oocytes ≥15) [9,10].…”
Section: Roc Curve Analysis For Forecasting Ovarian Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, our group (Oliveira et al, 2012; 2013) described an ovarian response prediction index (ORPI). The ORPI values were calculated by multiplying the AMH (ng/ml) level by the number of antral follicles (2-9 mm), and then by dividing the outcome by the patient's age (in years).…”
mentioning
confidence: 99%